ANALISIS PERAN GURU PAK SEBAGAI PENDIDIK DAN TELADAN DALAM MENANGANI PENGGUNAAN BAHASA TOKSIK DI SMKN 1 TANA TORAJA - Isak Karangan; Aprilia Saruran (JIP: Jurnal Ilmu Pendidikan, 2024)
Seeing the current phenomenon of using toxic language, this is one of the things that schools, especially Christian religious education teachers, need to pay attention to. Basically, the use of toxic language by students does not reflect the character of Christian youth. One of them is the use of toxic language by students at SMKN 1 Tana Toraja who as Christian teenagers should not use toxic language in communicating. This research aims to analyze the role of PAK teachers as educators, role models and leaders in dealing with the use of toxic language at SMKN 1 Tana Toraja. This research uses qualitative methods with interview techniques, literature and observation. The results of this research are that the Religious Education teacher at SMKN 1 Tana Toraja has carried out his role as an educator, leader, role model and communicator in dealing with the use of toxic language, however environmental factors and social media have become a means of spreading the use of toxic language.